Incidence of and Risk Factors for Central Venous Catheter Thrombosis: Results from a Single-Center Pediatric Intensive Care Unit - Maha Azzam; Yousef M. AlTalhi; Hani Alsawadi; Mohamed Humoodi; Abdullah Alzahrani; Amir Shehzad Hayat; Mohammed Bakhsh; Sara Osman (MDPI AG, 2024)
Background: Central Venous Catheter (CVC) is a necessary and important tool in managing acutely ill children and those needing complex care. CVC enables infusing venous medication, fluids, blood products, chemotherapy, total parental nutrition, and painless withdrawal of blood for laboratory testing when needed. Objective: To identify the incidence and risk factors for Central Venous Catheter-Related Thrombosis (CVC-RT) among patients admitted to the Pediatric Intensive Unit. Method: This was a prospective, observational, single-center study that was conducted over 17 months from September 2019 to January 2021 at King Abdulaziz Medical City, Jeddah. Design: Prospective observational study. Setting: King Abdulaziz Medical City, a tertiary care center in the western region of Saudi Arabia. Patients: Pediatric patients aged 1 to 168 months who were admitted to the PICU and required central line insertion (whether inserted centrally or peripherally) for more than 48 hours were included. Screening for thrombosis was performed within day 4-7 post-line insertion and again on the 14th day. Results: A total of 255 patients were enrolled over 17 months. The incidence rate of CVC-RT was 5.4%. The type of CVC was significantly different between the two groups; in the no thrombosis group, 59.2% had a central line while in the CVC-RT groups, 51.9% had a PIC line (p = 0.027). In a multivariate regression analysis including patients' clinical profile, high D-dimer as baseline and low platelets were both significant risk factors for CVC-RT [adjusted OR = 3.22, CI (1.25-8.28), p = 0.015 and adjusted OR = 7.38, CI (2.18-25.02), p = 0.001], respectively. Conclusions: The current study found that PIC line was associated with an increased risk of CVC-RT, which is congruent with the literature. As children with CVC can have multiple risk factors for developing CVC-RT, it is important to conduct further large prospective studies to identify such factors and decrease the incidence of CVC-RT.